The Impact of Organizational Resilience Development on Traffic Safety - József Orbán; Gyula Szabó (Engineering Proceedings)
This paper focuses on the goal of the Zero Vision initiative, which aims to reduce fatal traffic accidents to zero, and demonstrates how resilient operations and the continuous improvement of transportation systems can contribute to achieving this goal. It analyzes the tools for developing transportation resilience from various perspectives, including human factors, technology, regulation, and organizational culture. Additionally, it provides a detailed overview of the practical implementation of organizational resilience across different transport sectors, with particular attention paid to aviation and integrated disaster management. The development of organizational resilience contributes to strengthening safety culture, fostering innovation, managing risks, and reducing the number and severity of accidents.